ANALISIS PENGARUH PENGGUNAAN E-WALLET TERHADAP PERILAKU KONSUMEN (STUDI SEBAGIAN MASYARAKAT JAWA TIMUR) - nikmah, yuliani khoirun; Dias Satria (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
Technological developments are changing society's paradigm from conventional traditions to the digital era, making it possible to fulfill daily needs via smartphone devices. E-Wallet, as a form of digital wallet, is an important phenomenon that is influenced by companies in improving the quality of their applications. Payments with electronic money bring efficiency and a modern lifestyle, the impact of which can be seen in more impulsive consumer behavior. This research aims to explore the deeper impact of using E-Wallets on consumer behavior in the context of ease of transactions, and the extent to which this convenience can change shopping patterns into consumer behavior among the people of East Java who use E-wallets. The research method used is a quantitative approach with surveys (distributing questionnaires), and using the Partial Least Square (PLS) method. The results of this research imply that the ease of use of E-Wallet not only provides transaction efficiency but also economic potential for consumers in East Java. Price and habit factors influence consumer behavior more than E-Wallet performance expectations. Therefore, these findings provide valuable guidance for E-Wallet service providers to design appropriate and effective strategies in the East Java market.